A Mixed-Methods Needs Analysis of Maritime English Competencies: Aligning Maritime Transportation Management Students With Industry Expectations - Khafifah; Nurysam; Ratno; Nurlely Nasaruddin (Riviera Publishing, 2026)
This research examines the English language competencies required by industry stakeholders in the Maritime Transportation Management sector. A mixed-methods approach with a convergent design was employed, integrating quantitative and qualitative data to obtain a comprehensive understanding of industry needs. Data were collected through questionnaires, semi-structured interviews, and document analysis, involving 14 respondents, comprising maritime industry practitioners and representatives of educational institutions. The data were analyzed using descriptive statistics and thematic analysis through methodological triangulation. The findings indicate that speaking and listening skills are the primary competencies required in Maritime English, particularly for operational communication and workplace coordination. In addition, reading and writing skills are also considered essential for understanding and producing technical documents and professional correspondence. Mastery of maritime terminology and contextual translation skills is regarded as an important supporting competency, ensuring information accuracy and preventing miscommunication in professional settings. Therefore, a reorientation of the Maritime English syllabus toward a more contextual, applied, and professionally competency-based approach is necessary to enhance the readiness of Maritime Transportation Management graduates to meet the demands of the global maritime industry.